2021
DOI: 10.1186/s13102-021-00265-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between isokinetic knee torques and single-leg hop distances in three directions in patients after ACL reconstruction

Abstract: Background When planning rehabilitation and conditioning for performance enhancement and a return to sports after anterior cruciate ligament reconstruction, identifying the elements of physical function associated with single-leg hop is important. The purpose of this study was to clarify the relationship between single-leg hop distances in three directions and knee extensor and flexor strengths at 6 months after reconstruction. Methods Participants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The postoperative criterion-based rehabilitation protocol was conducted based on previous studies, 24,25 and all patients underwent the same protocol (Table 1). However, patients who underwent repair of the mid-posterior meniscus were not permitted to squat with the knee bent more than 90°until 3 months postoperatively.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative criterion-based rehabilitation protocol was conducted based on previous studies, 24,25 and all patients underwent the same protocol (Table 1). However, patients who underwent repair of the mid-posterior meniscus were not permitted to squat with the knee bent more than 90°until 3 months postoperatively.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…For open-chain exercises, the patient was instructed to avoid repeated knee extension exercises with maximum resistance near the ankle in the range of 30°to 10°of knee flexion in the sitting position for 3 months postoperatively. 24 Until then, patients mainly performed closed kinetic chain exercises and proprioceptive training. Jogging was permitted after 3 months, and the speed and distance of jogging were gradually increased according to joint effusion, symptoms, and muscle strength.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses 17 , 49 , 50 reported that the addition of ALLR to ACLR improves tibial rotational stability compared with isolated ACLR. In addition, as the muscle force generation capacity could improve dynamic joint stability, muscle performance, such as muscle strength and activation, could positively affect SLHD 23 , 47 , 51 , 52 . In the present study, muscle strength and AT for the quadriceps and hamstrings were better in the combined ACLR and ALLR versus isolated ACLR group.…”
Section: Discussionmentioning
confidence: 99%
“…The testing order for limbs began with the uninvolved side. Patients performed up to 15 extension and flexion repetitions (concentric/concentric action mode) for each leg at 180°/sec while in an upright sitting position, with the maximal torque value recorded (Nm/kg) 23 , 24 . Flexor and extensor strengths were determined as the quadriceps and hamstring muscle strengths, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The longest distance (cm) of the three trials was recorded. The ICC of the single measurement values of the surgical leg was in the range of 0.91‐0.99 30 . The distance was normalized by height (cm).…”
Section: Methodsmentioning
confidence: 99%